Síntese e caracterização morfológca, óptica e elétrica do compósito hidrogel/MBBA. - Silva, Keila Domingues Gomes (2009)
Hydrogels are materials based on hydrophilic tridimensional network (3D) with wide technological application. In the last decade the application has still more expanded due to the confinement on 3D matrix of materials such as magnetic particles, electrochromic moieties, enzymes, liquid crystals, nanostructured particles and others forming composites. Such composites present, often, the properties of hydrogels (hydrophilicity, biocompatibility, etc.) and, at same time, the properties associated to confined material on 3D network. In this dissertation, the electro-optic behaviors of following materials: polyacrylamide (PAAm) hydrogel, liquid crystal (MBBA) (N-[(4- metoxy benzilidene)-4-(buthyl aniline)]), a thermotropic liquid crystal, and composites obtained by the confinement of MBBA on PAAm 3D matrix. The hydrogels were synthesized in a sealed environment through photo-initiated radical polymerization chemical of acrylamide (AAm) monomers in presence of N',N'-methylene-bisacrylamide (MBAAm). The investigations of electro-optical properties were performed by the use of following techniques: electrical impedance spectroscopy (EIS), optical transmittance, light polarized optical microscopy (LPOM) and scanning electron microscopy (SEM). Thus, it was observed that the MBBA liquid crystal presents relaxation through permanent dipole, and the hydrogel of PAAm and the composites, formed by mixture of hydrogel + MBBA, present two different relaxations, one by dipolar and other by ionic movement. In spite of the relaxation time of hydrogel presents temperature dependence, such dependence disappears on the composite hydrogel/MBBA. This is a relevant fact that can be considered for future application in devices that should not change the electro-optic response as the temperature is changed.